Adiposidade corporal e atividade física em diabéticos tipo 2 com e sem hipertensão arterial - Codogno, Jamile Sanches; Fernandes, Romulo Araújo; Freitas Júnior, Ismael Forte; Amaral, Sandra Lia do; Monteiro, Henrique Luiz [UNESP] (My University, 2010)
The purpose of this study was to compare hemodynamic variables, physical activity and body composition between type 2 diabetics (T2DM) and type 2 diabetic and hypertensive ones (T2DM+AH), as well to analyze risk factors in both groups. Cross-sectional study, which analyzed 121 type 2 diabetic attended by two health care units from Bauru, Sao Paulo. Diabetics were divided into two groups: T2DM (n= 24) and T2DM+AH (n= 97). Domains of physical activity have been assessed by Baecke’s questionnaire. Blood pressure values, fasting glucose, body fatness, body mass index, waist circumference and waist-hip ratio have been assessed. T2DM+AH group presented higher values for body mass index (p= 0.001), waist circumference (p= 0.022), body fat percentage by bioelectrical impedance (p= 0.001) and fasting glucose (p= 0.029). Blood pressure was related to body composition indicators mainly in the T2DM+AH group. There was no diff erence in indicators of habitual physical activity. T2DM+AH subjects presented higher body fatness and fasting glucose than T2DM subjects. Moreover, in diabetic subjects the body composition seems to be determinant in the increase of blood pressure.

O objetivo deste estudo foi comparar variáveis hemodinâmicas, de atividade física e composição corporal entre diabéticos do tipo 2 (DM2) e diabéticos do tipo 2 com hipertensão (DM2+HA), bem como, analisar a relação entre indicadores risco nestes dois grupos. Estudo de delineamento transversal, o qual envolveu 121 diabéticos do tipo 2 cadastrados em duas unidades básicas de saúde da cidade de Bauru-SP. Os pacientes foram divididos em dois grupos: DM2 (n= 24) e DM2+HA (n= 97). A atividade física em diferentes domínios foi avaliada por meio do questionário de Baecke. Foram analisados valores de pressão arterial sistólica e diastólica, glicemia em jejum, gordura corporal, índice de massa corporal, circunferência de cintura e razão cintura/quadril. O grupo DM2+HA apresentou valores de índice de massa corporal (p= 0,001), circunferência de cintura (p= 0,022), percentual de gordura por impedância bioelétrica (p= 0,001) e glicemia em jejum (p= 0,029) mais elevados. A pressão arterial elevada se correlacionou positivamente com indicadores da composição corporal. Nos indicadores de atividade física habitual não se observou diferença signifi cante. O grupo DM2+HA apresentou maior gordura corporal e glicemia em jejum quando comparados aos portadores de DM2.
Keywords: Type 2 diabetes mellitus; Hypertension; Obesity; Physical activity; Diabetes mellitus tipo 2; Hipertensão; Obesidade; Atividade física